2022
DOI: 10.3389/fonc.2022.819128
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/mTOR Pathway and Its Role in Cancer Therapeutics: Are We Making Headway?

Abstract: Cancer is a severe public health issue that is a leading cause of mortality globally. It is also an impediment to improving life expectancy worldwide. Furthermore, the global burden of cancer incidence and death is continuously growing. Current therapeutic options are insufficient for patients, and tumor complexity and heterogeneity necessitate customized medicine or targeted therapy. It is critical to identify potential cancer therapeutic targets. Aberrant activation of the PI3K/AKT/mTOR pathway has a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
221
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(222 citation statements)
references
References 121 publications
(127 reference statements)
1
221
0
Order By: Relevance
“…Activated mTORC1 signaling may trigger recurrent reprograming that helps escape from glycolytic addiction in cancer cell lines from various solid tumor types ( Pusapati et al, 2016 ). Recently, treatments targeting PI3K/AKT/mTOR and mTORC1 pathways have emerged as promising strategies in cancer therapeutics ( Yang et al, 2019 ; Peng et al, 2022 ). Epithelial–mesenchymal transition (EMT) is a process that the majority of tumors have gone through during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated mTORC1 signaling may trigger recurrent reprograming that helps escape from glycolytic addiction in cancer cell lines from various solid tumor types ( Pusapati et al, 2016 ). Recently, treatments targeting PI3K/AKT/mTOR and mTORC1 pathways have emerged as promising strategies in cancer therapeutics ( Yang et al, 2019 ; Peng et al, 2022 ). Epithelial–mesenchymal transition (EMT) is a process that the majority of tumors have gone through during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, treatments targeting PI3K/AKT/mTOR and mTORC1 pathways have emerged as promising strategies in cancer therapeutics (Yang et al, 2019;Peng et al, 2022). Epithelial-mesenchymal transition (EMT) is a process that the majority of tumors have gone through during tumor progression.…”
Section: )mentioning
confidence: 99%
“…Targeting PI3K/AKT/mTOR pathway is considered one of the most signi cant approaches used as anticancer strategy. There are many PI3K/AKT/mTOR pathway-inhibiting compounds that are commercially available, and the barrier to their effectiveness is the body's resistance to these medications 40 . Down regulating the expression of proteins involved in PI3K/AKT/mTOR pathway leads to cell cycle arrest and apoptosis 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiation resistance and chemotherapy resistance lead to unsatisfactory treatment effects in some patients [ 146 ]. Due to the prominent role of the PI3K/AKT/mTOR pathway in cell proliferation and survival, inhibitors of this pathway are anticipated to be effective treatments for NPC [ 147 ]. Preclinical trials showed that PI3K inhibitors decreased cell proliferation, decreased xenograft tumour growth, and increased radiosensitivity [ 148 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%